Microstructural details in shells of the gastropod genera Carychiella and Carychium of the Middle Miocene. (8th June 2015) - Jochum, Adrienne; Neubauer, Thomas A.; Harzhauser, Mathias
Abstract : Microstructural details are revealed via scanning electron microscopy (SEM) in two carychiid species from the early Middle Miocene of Styria, SE Austria. The protoconchs of the shells of Carychiella eumicrum (Bourguignat 1857) and Carychium gibbum (Sandberger 1875) show different types of microstructure on the embryonic shell during ontogeny. Total, superficial punctate structure on the shell of Carychiella eumicrum contrasts with the protoconch–teleoconch demarcation (p/t boundary) observed on the protoconch of Carychium gibbum . Both species exhibit aragonitic microstructure. Diagenetic effects, prismatic, homogeneous and crossed lamellar microstructures are detectible in both species. Rheomorphic folding and dense pitting within the columella of Carychiella eumicrum suggest a structure–function relationship for tensile strength and bulk weight reduction in carychiid snails. We hypothesize that total superficial pitting on the shell of C. eumicum, seen here for the first time in the Carychiidae, suggests paedomorphosis as a life‐history strategy to palaeoecological conditions of the Rein Basin during the early Middle Miocene.